2018
DOI: 10.1111/bju.14531
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative analysis of robot‐assisted vs open simple prostatectomy for benign prostatic hyperplasia

Abstract: The results showed that RASP provided similar functional outcomes to those of OSP, whilst maintaining a good (or even better) safety profile. Our results suggest that RASP is a viable, efficient and potentially superior alternative to the open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…In line with existing studies, Mourmouris and co-workers reported of a longer operative time, shorter hospital stay and lower estimated blood loss for RASP patients. In this prospective comparative trial, a higher rate of grade ≥ 2 Clavien-Dindo complications in the OSP group could be observed [12]. Interestingly, the number of postoperative blood transfusions in our OSP cohort is higher than the one described in the literature (6.8-13%) [3,18,19].…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…In line with existing studies, Mourmouris and co-workers reported of a longer operative time, shorter hospital stay and lower estimated blood loss for RASP patients. In this prospective comparative trial, a higher rate of grade ≥ 2 Clavien-Dindo complications in the OSP group could be observed [12]. Interestingly, the number of postoperative blood transfusions in our OSP cohort is higher than the one described in the literature (6.8-13%) [3,18,19].…”
Section: Discussioncontrasting
confidence: 44%
“…In the prospective multicenter trial, Mourmouris et al reported also a transperitoneal approach. For enucleation, a vertical incision of the bladder and prostatic capsule was performed [12]. In contrast, we performed a transvesical approach to the adenoma without dropping the bladder off the pelvic wall in a transperitoneal approach, thus avoiding capsulotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four studies comparing RASP outcomes to OSP [36,[42][43][44][45] (Table 2). In all of these studies, the length of operation was significantly longer in RASP compared to OSP.…”
Section: Resultsmentioning
confidence: 99%
“…All 26 case studies [ 3 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] included in the final analysis were non comparative case series with level 3 evidence. In nine comparative studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], outcomes of RASP were compared to outcomes of other minimally invasive modalities (OSP, HoLEP, ThuVEP) for the treatment of benign prostate hyperplasia (BPH). Unfortunately, there have been no randomized clinical trials among these studies conducted to date.…”
Section: Resultsmentioning
confidence: 99%